The Analysis of Carrying Capacity for Agricultural Land in Tanah Datar District - Sinaga, Barita; Dewata, Indang (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
ABSTRACT : This research aimed to find out the amount of carrying capacity for agricultural land in supporting food self-sufficiency in Tanah Datar District. Data analysis used is the level of carrying capacity for the agricultural land. The result of the study shows that the level of carrying capacity of agricultural land in Tanah Datar District is 3,5 with the lowest level of carrying capacity of agricultural land located in Lima Kaum sub-district which is 2,19 and the highest in Pariangan sub-district which is 5,49. This means that Tanah Datar District has been able to implement food self-sufficiency. The benefit of this research is expected to contribute the idea for the government of Tanah Datar District and other related instances in food security and overcoming land conversion, so that will not cause the problem in land carrying capacity toward food self-sufficiency. This research is expected to contribute in developing knowledge of area and economic land resources. Keywords: Analysis, Carrying Capacity, Agricultural Land.